The Effect Of The Application Of The Problem Based Learning (Pbl) Model On Students' Learning Outcomes On Ecosystem Material In Grade Xi Of Sma Negeri 2 Pangkatan - Diah Apriana Ritonga, Wita Ferwati, Basyarul Ulya (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to analyze the effect of applying the Problem-Based Learning (PBL) model on student learning outcomes in ecosystem material in class XI MIPA SMA Negeri 2 Pangkatannya. The research method used is quasi-experimental with a Nonequivalent Control Group Design. The research sample consisted of two classes, namely class XI MIPA 3 as an experimental class using the PBL model and class XI MIPA 2 as a control class using a conventional learning model. Data was collected through pretest and posttest, which were then analyzed using t-test and N-Gain calculation to see the improvement of student learning outcomes. The results showed that the average pretest score of the experimental class was 62.4, while the control class was 60.8. After treatment, the average posttest score of the experimental class increased to 84.6, while the control class only reached 75.2. The N-Gain analysis showed a higher increase in learning outcomes in the experimental class with a value of 0.65 (moderate category), compared to the control class which only reached 0.48 (moderate category). The t-test showed a significant difference between the learning outcomes of the two classes with a value of t_count = 3.89> t_table = 2.00 at a significance level of 0.05, which means that the PBL model has a significant positive effect on student learning outcomes. Based on the research results, the PBL model is recommended as an effective learning strategy for improving students' understanding, especially in ecosystem material